Economic Impact of Cooperative Membership on Women Dairy Farmers: Evidence from the Mulkanoor Women Dairy Cooperative, Telangana, India - , Jesna Jaleel, K Sravanthi, T Lavanya, B Savitha (Archives of Current Research International, 2025)
Aims: To identify the determinants of cooperative membership among women dairy farmers in the Mulkanoor Women Dairy Cooperative and to assess its impact on milk yield, price received, production cost, and net returns. Study Design: Cross-sectional primary survey combined with econometric impact evaluation using Propensity Score Matching (PSM). Place and Duration of Study: The study was conducted in the three districts of Telangana -Hanumakonda, Karimnagar and Siddipet where the Mulkanoor Women Dairy Cooperative is active. Data collection was carried out from April to July 2025. Methodology: The study sample consisted of 180 women dairy farmers—90 cooperative members and 90 non-members—selected through multistage random sampling from 18 villages in three districts, with 60 respondents drawn from each district. Data on socio-economic characteristics, milk productivity, prices, and costs were obtained via structured interviews. A binary logistic regression model was used to identify factors influencing cooperative membership. To estimate the economic impact of membership, Propensity Score Matching (nearest neighbour, kernel, and caliper methods) was applied to control for selection bias. Matching quality was evaluated using balance diagnostics such as standardized mean bias, t-tests, pseudo-R², and joint significance tests. Outcome variables included net cost per litre, net income per litre, milk yield (L/animal/day), and price received (Rs/L). Results: Logistic regression results showed that age (with a non‑linear effect), dairy experience, landholding size, proximity to collection centres, and herd size significantly influenced membership, while education and household size did not. Propensity Score Matching analysis confirmed strong covariate balance and highlighted significant economic advantages for cooperative members. The net cost of milk production was considerably lower for members (Rs. 17.75/litre) compared to non-members (Rs. 31.39/litre), reflecting cost savings of Rs. 14–17 per litre. Although the base price received by members was about Rs. 15/litre lower than prevailing market rates, bonus incentives (Rs. 14 per Rs. 100 worth of milk sold) combined with reduced production costs (Rs. 12–15/litre less) enhanced their net returns by approximately Rs. 6/litre. Moreover, members demonstrated significantly higher productivity, producing about 6 litres more milk per animal per day than non-members, a difference confirmed to be statistically significant by the Average Treatment Effect on the Treated (ATT) estimates. Conclusion: Membership in the Mulkanoor Women Dairy Cooperative has a significant positive economic impact by enhancing milk productivity, lowering production costs, and increasing net returns for women dairy farmers. These findings underscore women‑led cooperatives as effective mechanisms for driving inclusive and sustainable rural economic growth. Key policy implications include the need to support women-led cooperatives through targeted credit facilities, improved infrastructure, capacity-building programs, and integration into broader dairy value chains to amplify productivity and income stability.